2013
DOI: 10.1371/journal.pone.0055326
|View full text |Cite
|
Sign up to set email alerts
|

Relative Susceptibility of Vitis vinifera Cultivars to Vector-Borne Xylella fastidiosa through Time

Abstract: Understanding the interactions between pathogen, crop and vector are necessary for the development of disease control practices of vector-borne pathogens. For instance, resistant plant genotypes can help constrain disease symptoms due to infections and limit pathogen spread by vectors. On the other hand, genotypes susceptible to infection may increase pathogen spread owing to their greater pathogen quantity, regardless of their symptom status. In this study, we evaluated under greenhouse conditions the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…However, most of these do not use natural transmission by the vector. For example, Xylella fastidiosa was mechanically (needle) inoculated in order to evaluate the relative susceptibility of different grapevine cultivars (Rashed et al, 2013). The phytoplasmas Candidatus Phytoplasma ( Ca.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these do not use natural transmission by the vector. For example, Xylella fastidiosa was mechanically (needle) inoculated in order to evaluate the relative susceptibility of different grapevine cultivars (Rashed et al, 2013). The phytoplasmas Candidatus Phytoplasma ( Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have shown that different species, breeds, cultivars, or ecotypes respond differently to infection in terms of disease symptom severity, mortality, or performance (Råberg et al 2007, 2009, Rashed et al 2013). These differences may be caused by variability in pathogen resistance, tolerance, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty microlitres of a suspension (10 9 cells ml À1 ) of each strain were used to mechanically inoculate 6-month-old grapevines at the stem base using standard procedures [16]. Inoculations were performed twice (experimental blocks), 15 plants were inoculated in each block and the plants were maintained as described previously [28]. Eight weeks after inoculation, petioles were removed from immediately adjacent to the inoculation point as well as 15 cm above the point of inoculation.…”
Section: Plant Host Colonizationmentioning
confidence: 99%